1979
DOI: 10.1148/130.2.421
|View full text |Cite
|
Sign up to set email alerts
|

Critical Evaluation of99mTc Glucoheptonate as a Brain Imaging Agent

Abstract: 99mTc glucoheptonate was used as a brain imaging agent in a consecutive series of 859 patients. Sensitivity was 94% in patients with proved CNS tumors. Static imaging of patients with infarction showed a sensitivity of 62%. When the perfusion study was included, this valve increased to 90%. Overall sensitivity was 83%, specificity 99%, and accuracy 95% without inclusion of perfusion results. When these results were included, overall sensitivity was 93%, specificity 99%, and accuracy 98%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The uptake of 99mTc-GHA in viable tumor increases with time whereas it clears rapidly from inflammatory lesions. [ 22 ]…”
Section: Mechanism Of 99m-technetium-glucoheptonate Uptake In Brain Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The uptake of 99mTc-GHA in viable tumor increases with time whereas it clears rapidly from inflammatory lesions. [ 22 ]…”
Section: Mechanism Of 99m-technetium-glucoheptonate Uptake In Brain Tmentioning
confidence: 99%
“…They reported that a combination of several factors such as enhanced blood clearance, effective penetration of the BBB, active uptake by tumoral tissue and tissue binding forms the basis of brain tumor imaging with 99mTc-GHA. [ 22 ] Barai et al . in their study found 99mTc-GHA SPECT to be an effective imaging modality for detecting recurrent glioma in patients treated with radiotherapy.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Older studies that evaluated the mechanism of uptake in proximal tubular cells of the kidney suggest that Tc99m-glucoheptonate uptake is dependent on cellular metabolism. 21 Leveille et al 22 suggested that glucoheptonate may also act as a substrate for malignant tissue and Tanasescu et al 23 suggested the possibility of intracellular binding of glucoheptonate. In the present study, Tc99m-glucoheptonate uptake was not noted in normal brain tissue, so the possibility that glucoheptonate may be a substrate for malignant tissue (and considering its close structural similarity to D D-glucose) and/or intracellular binding seems likely in medulloblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Tanasescu et al 23 used Tc99m-glucoheptonate as a brain imaging agent in a consecutive series of 859 patients with an overall sensitivity of 93%, specificity 99% and accuracy 98% in brain tumours. O'Tuama et al reported the diagnostic accuracy of Thallium-201 and Tc99m-MIBI in 19 children.…”
Section: Discussionmentioning
confidence: 99%
“…In as early as 1975, Tanasescu, et al .,[6] showed the utility of Tc-GH as a brain scanning agent. Lιveillι, et al .,[7] described Tc-GH as an important advance in brain tumor detection.…”
Section: Introductionmentioning
confidence: 99%